2017
DOI: 10.3390/brainsci7100135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Predictive Factors on Minors’ Mental Health According to the Spanish National Health Survey

Abstract: Research on minors’ mental health is an increasingly developing area. Given the increased prevalence of disorders, it seems necessary to analyze the factors that can affect poor mental health. This study analyzes the influence of occupational class, educational level, age, sex and perceived mental health of Spanish children, which is measured through the Strengths and Difficulties Questionnaire. The sample consists of 3599 minors between 4 and 14 years old, who were interviewed through the Spanish National Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…For the studies that have related occupational class of parents with mental health, three social classes are frequently used: high, medium, and low [ 5 ]. The results show that those jobs of the primary wage earner with lower categories are those most related to the presence of mental health problems in children [ 17 ], where parental rejection was more prevalent among parents with little education and a low family socio-economic level [ 18 ]. On the contrary, it is the families with jobs corresponding to the middle and the most privileged classes that become a higher protective factor against the presence of mental health problems in the minors than those linked to disadvantaged classes [ 12 , 13 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the studies that have related occupational class of parents with mental health, three social classes are frequently used: high, medium, and low [ 5 ]. The results show that those jobs of the primary wage earner with lower categories are those most related to the presence of mental health problems in children [ 17 ], where parental rejection was more prevalent among parents with little education and a low family socio-economic level [ 18 ]. On the contrary, it is the families with jobs corresponding to the middle and the most privileged classes that become a higher protective factor against the presence of mental health problems in the minors than those linked to disadvantaged classes [ 12 , 13 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that those jobs of the primary wage earner with lower categories are those most related to the presence of mental health problems in children [ 17 ], where parental rejection was more prevalent among parents with little education and a low family socio-economic level [ 18 ]. On the contrary, it is the families with jobs corresponding to the middle and the most privileged classes that become a higher protective factor against the presence of mental health problems in the minors than those linked to disadvantaged classes [ 12 , 13 , 15 , 17 ]. In general, those children with families with poorer socioeconomic status have worse physical and mental health than those with a higher socioeconomic level [ 14 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the international agreement for the application of the Strengths and Difficulties Questionnaire (SDQ) [18], or the measurement of mental health, has represented an advance in research coordination within the scientific community [19], always with the precaution of the possible effects that cultural differences may have on the results [20,21]. This questionnaire has been validated internationally [4,15,22,23,24,25] and has been used in a multitude of studies to measure mental health both longitudinally [4,26], and transversally [14,27]. It has proven to be an excellent screening tool compared to other more classic tools, such as the Child Behavior Checklist (CBCL) [28,29].…”
Section: Methodsmentioning
confidence: 99%
“…In Spain, it was introduced for the first time in the National Health Survey of 2006 to study the mental health of children. In addition to the 2006 Spanish National Health Survey, ENSE 2006 [13,15,38,39], it has also been used in subsequent counterpart studies, ENSE 2011-2012 [14,34]. Therefore, it can be concluded that the SDQ-parent is an internationally recognized instrument with excellent quality for the screening of children with problems or difficulties in mental health [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation